Profitability of important summer vegetables in Keranigonj upazilla of Bangladesh - Hasan, MR; Bai, HU; Islam, MA (Journal of the Bangladesh Agricultural University, 2014)
The study was conducted in Keranigonj upazilla under Dhaka district from the month of April to May in 2014 to determine the cost and return of some important vegetables namely bottle gourd, brinjal and cucumber. Data were collected from 20 bottle gourd farmers, 30 brinjal farmers and 20 cucumber farmers by using purposive sampling method. The averages total cost per hectare were calculated at Tk. 4,12,713, Tk. 2,69,627 and Tk.2,56,258 for bottle gourd, brinjal and cucumber production.Net return per hectare was the highest for brinjal (Tk. 7,32,811) and the lowest for bottle gourd (Tk. 5,79,431).The benefit cost ratios (BCR) considering variable cost were 2.83, 4.88 and 4.57 for bottle gourd, brinjal and cucumber respectively. The highest BCR was for brinjal (3.72) and the lowest for bottle gourd (2.40) on the basis of total cost. Lack of capital, low price of vegetables, high price of input, price fluctuation, disease, unavailability of input and lack of storage facilities were the major problems of farmers. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21400 J. Bangladesh Agril. Univ. 12(1): 111-118, June 2014